Orchestration of Angiogenesis by Immune Cells - Bruno, Antonino; Pagani, Arianna; Pulze, Laura; Albini, Adriana; Dallaglio, Katiuscia; Noonan, Douglas M.; Mortara, Lorenzo (Frontiers in Oncology, 2014)
It is widely accepted that the tumor microenvironment plays a major role in cancer and is indispensable for tumor progression. The tumor microenvironment involves many “players” going well beyond the malignant-transformed cells, including stromal, immune and endothelial cells. The non-malignant cells can acquire tumor-promoting functions during carcinogenesis. In particular, these cells can “orchestrate” the “symphony” of the angiogenic switch, permitting the creation of new blood vessels that allows rapid expansion and progression toward malignancy. Considerable attention within the context of tumor angiogenesis should focus not only on the endothelial cells, representing a fundamental unit, but also on immune cells and on the inflammatory tumor infiltrate. Immune cells infiltrating tumors typically show a tumor-induced polarization associated with attenuation of anti-tumor functions and generation of pro-tumor activities, among these angiogenesis. Here we propose a scenario suggesting that the angiogenic switch is an immune switch arising from the pro-angiogenic polarization of immune cells. This view links immunity, inflammation and angiogenesis to tumor progression. Here we review the data in the literature and seek to identify the “conductors” of this “orchestra”. We also suggest that interrupting the immune -> inflammation -> angiogenesis -> tumor progression process can delay or prevent tumor insurgence and malignant disease.